Increased Myocardial Oxygen Consumption Precedes Contractile Dysfunction in Hypertrophic Cardiomyopathy Caused by Pathogenic TNNT2 Gene Variants. Issue 8 (21st April 2020) - Parbhudayal, Rahana Y.; Harms, Hendrik J.; Michels, Michelle; van Rossum, Albert C.; Germans, Tjeerd; van der Velden, Jolanda
Abstract : Background: Hypertrophic cardiomyopathy is caused by pathogenic sarcomere gene variants. Individuals with a thin‐filament variant present with milder hypertrophy than carriers of thick‐filament variants, although prognosis is poorer. Herein, we defined if decreased energetic status of the heart is an early pathomechanism in TNNT2 (troponin T gene) variant carriers. Methods and Results: Fourteen individuals with TNNT2 variants (genotype positive), without left ventricular hypertrophy (G+/LVH−; n=6) and with LVH (G+/LVH+; n=8) and 14 healthy controls were included. All participants underwent cardiac magnetic resonance and [ 11 C]‐acetate positron emission tomography imaging to assess LV myocardial oxygen consumption, contractile parameters and myocardial external efficiency. Cardiac efficiency was significantly reduced compared with controls in G+/LVH− and G+/LVH+. Lower myocardial external efficiency in G+/LVH− is explained by higher global and regional oxygen consumption compared with controls without changes in contractile parameters. Reduced myocardial external efficiency in G+/LVH+ is explained by the increase in LV mass and higher oxygen consumption. Septal oxygen consumption was significantly lower in G+/LVH+ compared with G+/LVH−. Although LV ejection fraction was higher in G+/LVH+, both systolic and diastolic strain parameters were lower compared with controls, which was most evident in the hypertrophied septal wall. Conclusions: Using cardiac magnetic resonance and [ 11 C]‐acetate positron emission tomography imaging, we show that G+/LVH− have an initial increase in oxygen consumption preceding contractile dysfunction and cardiac hypertrophy, followed by a decline in oxygen consumption in G+/LVH+. This suggests that high oxygen consumption and reduced myocardial external efficiency characterize the early gene variant–mediated disease mechanisms that may be used for early diagnosis and development of preventive treatments.